Success and satisfaction in the career: an analysis with higher education teachers - Rosa, Luciana Aparecida Barbieri da; Dias, Elaine Ortiz; Campos, Waleska Yone Yamakawa Zavatti; Godoy, Tais Pentiado; Hoffmann, Celina Franco; Rodrigues, Maria Carolina Martins (Revista de Administração da UFSM, 2021)
Objective: This study seeks to identify the perceptions of teachers at a Higher Education Institution concerning career satisfaction. Methodology: a survey was carried out on how much quantitative and adapted study by Costa (2014). The results show the need for constant improvement of the face of the teaching career, and the results show that the required competencies are associated with the perception of justice regarding the occupation of new associated hierarchical and evaluation systems, in addition, it stands out for the perception of stability career. Results: from an inferential point of view, the results show that happiness in professional life and hair positively affected shared teamwork through a good network of professional contacts and happiness in personal and family life. Practical implications: for future studies, it is suggested the expansion or scope of the research for teachers of all courses of the Institution under analysis. Originality/value: reflected on aspects related to the career, highlighting that professional identity is associated with the feeling of pride provided by the exercise of the profession, since the effects generated have an impact on the development and evolution of society.